DISPOSABLE CONTACT LENS-BASED OCULAR DELIVERY OF MOXIFLOXACIN : A NOVEL APPROACH - SHARMA, UMESH KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: In the present research, the main objective was to investigate the possibility of designing, fabricating, and optimizing a disposable ocular film-based drug delivery system. Methods: Moxifloxacin hydrochloride was loaded onto the prepared disposable ocular films by the soaking method. Results: The drug loading conditions were studied, and it was found that the maximum drug loading was achieved in 3 hours at pH 6.5 of the drug solution. It was also observed that the drug loading efficacy and in vitro drug release profile can be monitored by varying the ocular film composition. The ocular films were then characterized for thickness uniformity, size uniformity, weight uniformity, swelling index, surface pH, breaking on elongation, folding endurance, bio-adhesive strength, transparency, drug loading efficiency, moisture content, morphological characteristics, and in vitro drug release profiles. Conclusion: Based on the results, it was concluded that the developed disposable ocular films demonstrate a significant prolonged drug release within the therapeutic range of up to 12 h, which is promising as a novel disposable contact lens-based ocular drug delivery system.